QUANTIFYING PORE TYPES AND MICROPOROSITY EFFECTS BASED ON ELASTIC PROPERTIES ANALYSIS OF OFFSHORE SARAWAK CARBONATE RESERVOIR - BIN ZANURI , MUHAMMAD NUR ARIF (Universiti Teknologi PETRONAS, 2014)
Velocity and density as basis of modulus components on any rock formations are effected by the rock matrix, the pore geometry and also the fluids saturated in the formations. In carbonate formations, complex porosity dominates comprises of fractures, vugs, and moldic porosity which are the main identities which alter the elastic moduli response and creates confusions in seismic interpretations. One of the way to solve this problems is by quantifying the effects of each soft and stiff micro-porosity components in the reservoirs using the interpolation of Kuster-Toksoz-Differential effective medium (DEM) formulations. Kumar and Han (2005), found that the reference lines of Kuster-Toksoz formulations intersects with Wyllie-time average equations for intergranular porosity, whereas the stiff and soft bound are comparable with HashinStrickman bound. By that, we proposed to use simpler formulations of modified HashinStrickman bounds associated with Wyllie-time-average to quantify the pore geometry with some modifications and adjustments to restrict the parameters of the pore characterizations criteria. This gives the aspect ratio parameters needed in scattering theory of Kuster-Toksoz to model the dry rock modulus before fluid substitutions are conducted using Gassman’s formulations. The technique in used were conducted to model a well located in Central Luconia. The results gives a high similarities with the original bulk velocity curve and enable the relations of the carbonate properties and their resulting seismic response to be analyze.